IMPACT OF CIRCULAR ECONOMY INDICATORS ON RESOURCE PRODUCTIVITY IN EU COUNTRIES - Daniela Rybárová; Helena Majdúchová (Trendy v podnikání)
This study investigates the impact of circular economy indicators on resource productivity across European Union countries from 2012 to 2023. Using panel data analysis and quantile regression for panel data (QRPD), we explore how factors such as investments, gross value added (GVA), patents, material footprint, and circular material use rate affect resource productivity at different points of the distribution. The results reveal significant variations, indicating that investments have a more substantial impact at lower productivity levels, while innovation (measured through patents) plays a crucial role in higher productivity contexts. Additionally, the CART (Classification and Regression Trees) method was used to segment countries into groups, with radar charts employed for visual comparison of strengths and weaknesses. Our findings highlight the need for tailored policies to enhance circular economy practices, suggesting that a focus on both quantitative and qualitative approaches can provide a more comprehensive understanding of the economic, social, and environmental impacts. The study's insights can inform policymakers on strategies to improve resource efficiency and support sustainable development within the EU.